INFLUENCE OF TECHNOLOGICAL FACTORS ON THE STRUCTURE AND CHARACTERISTICS OF CASTINGS OF HIGH-MANGANESE STEEL - A. I. Garost (Литьë и металлургия)
The ways of optimization of the technological factors for receiving of high-manganese steel with increased exploitation characteristics are offered. The influence of addition elements of nitrogen on the structure, mechanical and exploitation characteristics is studied.